IgE Sensitization to Aspergillus fumigatus Is Associated with Reduced Lung Function in Asthma - Fairs, Abbie; Agbetile, Joshua; Hargadon, Beverley; Bourne, Michelle; Monteiro, William R.; Brightling, Christopher E.; Bradding, Peter; Green, Ruth H.; Mutalithas, Kugathasan; Desai, Dhananjay; Pavord, Ian D.; Wardlaw, Andrew J.; et al. (American journal of respiratory and critical care medicine, 2010)
The importance of Aspergillus fumigatus sensitization and colonization of the airways in patients with asthma is unclear. To define the relationship between the clinical and laboratory features of A. fumigatus-associated asthma. We studied 79 patients with asthma (89% classed as GINA 4 or 5) classified into 3 groups according to A. fumigatus sensitization: (1) IgE-sensitized (immediate cutaneous reactivity > 3 mm and/or IgE > 0.35 kU/L); (2) IgG-only-sensitized (IgG > 40 mg/L); and (3) nonsensitized. These were compared with 14 healthy control subjects. Sputum culture was focused toward detection of A. fumigatus and compared with clinical assessment data. A. fumigatus was cultured from 63% of IgE-sensitized patients with asthma (n = 40), 39% of IgG-only-sensitized patients with asthma (n = 13), 31% of nonsensitized patients with asthma (n = 26) and 7% of healthy control subjects (n = 14). Patients sensitized to A. fumigatus compared with nonsensitized patients with asthma had lower lung function (postbronchodilator FEV₁ % predicted, mean [SEM]: 68 [±5]% versus 88 [±5]%; P < 0.05), more bronchiectasis (68% versus 35%; P < 0.05), and more sputum neutrophils (median [interquartile range]: 80.9 [50.1-94.1]% versus 49.5 [21.2-71.4]%; P < 0.01). In a multilinear regression model, A. fumigatus-IgE sensitization and sputum neutrophil differential cell count were important predictors of lung function (P = 0.016), supported by culture of A. fumigatus (P = 0.046) and eosinophil differential cell count (P = 0.024). A. fumigatus detection in sputum is associated with A. fumigatus-IgE sensitization, neutrophilic airway inflammation, and reduced lung function. This supports the concept that development of fixed airflow obstruction in asthma is consequent upon the damaging effects of airway colonization with A. fumigatus.